The Use of Storybook to Improve the Grasp and Pronunciation of Action Words in Primary ESL Classroom - Abbas Nurain Abu; Li Li Kee (Journal of Teaching and Education, 2025)
The purpose of this action research was to investigate the use of storybooks to enhance the vocabulary and pronunciation skills of Year 4 pupils in primary ESL classroom, while also improving the teaching practices of the researcher. The data collection methods included pre- and post-action tests, semi-structured interviews, and observations, with data revision conducted through the triangulation method. The findings indicated that the implementation of storybooks positively impacted the pupils’ vocabulary and their ability to correctly pronounce action words. The researcher was also able to improve her teaching practices to better facilitate her pupils’ vocabulary development, particularly in the area of action words.